The Use of ICTs by Children and Young People with Mental Retardation and Syndrome Down in Domains of their Daily Life - Dimitropoulos, Christos; Katsigera-Svoronou, Christine; Rizou, Anastasia; Hantziara, Sofia Maria; Hasioti, Areti; Loukeris, Dionysis; Drigas, Athanasios (Technium Sustainability, 2022)
In this paper, we present a study, which revolves around the importance of Information and Communication Technologies (ICTs) at people with Intellectual Impairments. The goal of the study was to unveil how people with disabilities, such as Mental Retardation and Syndrome Down could use ICTs in order to enhance and facilitate their teaching, learning and everyday lifestyle. ICTs will be potentially a tool towards overcoming difficulties of these individuals. These people require ICTs systems highly configurable and adaptable to their personal needs. Otherwise, they will not be useful at all.